Wŏnhyo's philosophy of mind - Wŏnhyo, 617-686 (International Association of Wŏnhyo Studies' collected works of Wŏnhyo, 2012)
Leading East Asian Buddhist thinkers of the seventh century compared, analyzed, and finalized seminal epistemological and soteriological issues that had been under discussion in India and East Asia for centuries. The great Silla scholiast Wŏnhyo (617-686) was very much at the centre of the intense discussion and debate that occurred on these topics. This volume includes four of Wŏnhyo's works that are especially revelatory of his treatment of the complex flow of ideas in his generation.